SEMIOTICS, RHETORICAL LANGUAGE, AND FIGURATIVE LANGUAGE OF W.S RENDRA’S POETRY - M. Arifin Zaidin; Patmawati Halim (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2023)
Semiotic analysis of the poems